Pembinaan Kewirausahaan Meningkatkan Daya Saing Produk Kerupuk di Kecamatan Binawidya Melalui Teknologi IoT - Juandi Juandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This community service activity aims to foster entrepreneurship in Binawidya District, focusing on enhancing the competitiveness of cracker products through the application of Internet of Things (IoT) technology. To improve quality and production efficiency, we conducted training sessions that included fundamental understanding of IoT technology, implementation of production monitoring systems, and utilization of data for better decision-making. Through this approach, business actors are expected to optimize production process management, enhance product quality, and expand market reach. The results of this activity indicate an increase in knowledge and skills among entrepreneurs in using technology, as well as a positive impact on the competitiveness of cracker products in the local market. Thus, this program not only contributes to the development of SMEs but also promotes economic growth in Binawidya District.